The digital library in the re-inscription of African cultural heritage. (October 2015) - Peters, Dale; Brenzinger, Matthias; Meyer, Renate; Noble, Amanda; Zimmer, Niklas
African digital libraries have evolved beyond the 'preservation or access' debate of the 1990s, and the concomitant compulsion to (un-)systematically convert cultural heritage collections from analogue to digital formats. The challenge now lies in the agility to respond to user needs, to match the selection for digitisation with a more strategic approach towards research relevance and potential research outputs. This paper will examine the symbiotic relationship between preservation, cultural heritage and scholarship in a case study on the description and documentation of extinct African languages. It proposes that the new point of focus lies in digital scholarship, enabling both technical innovation and more intellectual engagement in revisiting the digital library to review, correct and augment transitory records through a new scholarly interpretation of African cultural heritage.